Cinematerapia: uma proposta psicoeducativa segundo a teoria de Jeffrey Young - Arantes, Carolina Faria (2014)
The objective of this research was to present to the cognitive-behavioral therapists a cinematherapeutic technique, based on the Disney animated films, which can be used for children and adolescents for psychoeducate about the entitlement / grandiosity scheme and insufficient self-control/self-discipline scheme, which make up the impaired limits domains, according to the theory Jeffrey Young. Seven experts professional in the clinical area of cognitive-behavioral approach aged between 26 to 47 years (= 33; DP = 8,01) and average acting time of = 9 anos (DP = 7,1). All participants had evidence of specialization in Cognitive-Behavioral Therapy (CBT), 29% had master\'s degree and 29% had postdoctoral. The instrument used was a test of judges composed of the transcription of verbal and nonverbal content of 19 scenes relative to the movies Cars , Beauty and the Beast , Wreck-It Ralph and Brave . Judges should read and judge which category was being portrayed in the scene at issue: entitlement / grandiosity scheme or insufficient self-control/self-discipline scheme. Data collected by test judges that these were nominal variables were transformed into binomial variables and then analyzed using the Wilcoxon test. The results indicated which scenes had a prevalence of impaired limits schema domain. Regarding the movie \"Cars\" was found predominance of entitlement / grandiosity scheme in three scenes; in \"Beauty and the Beast\" three scenes were representative of entitlement / grandiosity scheme and two about insufficient self-control/self-discipline scheme; in Wreck-It Ralph four scenes were considered examples of such schemes, three relating to insufficient self-control/self-discipline scheme and one concerning the entitlement / grandiosity scheme; finally, on Brave prevalence of insufficient self-control/self-discipline scheme was found in two scenes. In total was found a predominance of the impaired limits schemes characteristics in 14 scenes, which are represented by speech and nonverbal language of the characters. These scenes can be used to psychoeducate children and adolescents about these schemes. The use of tools able to engage the child and arouse their interest is very important in cognitive play therapy and is known to that the cinematherapy has a high potential for motivating patients. Psychoeducation is an essential practice in CBT because can affect adherence to treatment and enables the achievement of the other aim of therapy. Therefore, applying the cinematherapy in psychoeducation for children and adolescents contributes to increasing the effectiveness of the therapeutic process. This work contributes to expanding the arsenal of cognitive-behavioral techniques, as it suggests scenes that can be used as psychoeducational tools in the cognitive play therapy, based on a systematic categorization.